Case report: Androgen-secreting adrenocortical tumors in eight cats - Erger, Caylen G.; Gerras, Allison L.; Conley, Alan J.; Gilor, Chen; Burns DeMarle, Karah; Refsal, Kent R.; Fleming, Jamie M.; Sledge, Dodd G.; Langlois, Daniel K. (Frontiers in Veterinary Science, 2023)
Urine marking, aggression, and other behavioral concerns are common reasons for cat owners to seek veterinary care. Empiric treatment for lower urinary tract disease or primary behavior disorders are commonly pursued, especially in those cases with normal routine laboratory evaluations. Herein, we report the clinicopathologic findings in 8 sexually altered cats that were diagnosed with androgen-secreting adrenocortical tumors. Nearly all cats (n = 7) initially were evaluated for inappropriate urination and pungent urine, with additional behavioral concerns including aggression (n = 3) and excess vocalization (n = 4) commonly reported. Penile barbs (n = 5) were identified in all 5 male cats, and an enlarged clitoris was observed in 1 female cat. Testing of serum androgen concentrations revealed abnormally high androstenedione (n = 1) or testosterone (n = 7) concentrations. In the 5 cases with available adrenal tissue, histopathologic evaluation identified either an adrenocortical adenoma (n = 3) or adrenocortical carcinoma (n = 2). Hormonal abnormalities resolved and clinical signs improved in the 4 cats that underwent surgical adrenalectomy, with each of these cats surviving > 1 year. However, clinical signs were minimally impacted with medical treatments, including 1 cat in which trilostane treatment failed to improve clinical signs or testosterone concentrations. This collection of cases underscores the importance of a detailed physical examination as well as the consideration of endocrine disturbances in cats undergoing evaluation for inappropriate urination or aggression. Furthermore, this report adds to the growing body of evidence that sex-hormone secreting adrenal tumors in cats may be an under-recognized syndrome.